(untitled) (Bangladesh Journal of Animal Science, 2015)
The present study was conducted to know the morphology, morphometry, production and reproduction potentialities of Nageswari duck, an indigenous duck genetic resource of Bangladesh. Data on 58 representative adult Nageswari ducks were included for morphological study from 24 duck owners and two government organizations having Nageswari duck flocks while 468 individuals were considered for the traits of productive and reproductive performances. Information was collected by using a structured questionnaire through personal interaction, on spot recording and direct phenotypic measurements in five different regions of Bangladesh. Black plumage color with white stripe extended from neck to breast make unique features of Nageswari duck compared to other indigenous ducks. Morphometric measurements on adult live weight, body length, head diameter, bill length, neck length, shank length, wing length, massiveness and condition index in male and female were found to be 1.66±0.07 and 1.51±0.05 kg, 26.27±0.57 and 23.79±0.39 cm, 3.49±0.02 and 3.36±0.04 cm, 5.87±0.09 and 5.54±0.07 cm, 23.49±0.58 and 21.59±0.49 cm, 5.76±0.12 and 5.16±0.11 cm, 24.58±0.49 and 21.99±0.53 cm, 6.33±0.28 and 6.39±0.22, and 6.72±0.23 and 6.93±0.23 respectively. Age at first egg of Nageswari duck was found to be 168.48±3.53 days. Total number of eggs laid per year averaged 173.63±3.39 and peak production was found in 29.46±0.19 weeks. The average egg weight was estimated to be 67.32±0.82 g and characteristic bluish tinge of egg color was observed. Breed specific characteristic features and production profiles were observed in this study. The present study provided some baseline information on Nageswari duck of Bangladesh which could be useful for genetic characterization, conservation and future improvement programs in Bangladesh. Bang. J. Anim. Sci. 2015. 44(2): 92-99